A 5-Year retrospective analysis of adverse events in dentistry at the Dental Hospital, Faculty of Dentistry, Chulalongkorn University - Kiti Siriwatana; Sathirakorn Pongpanich (BMC, 2024)
Abstract Background Patient safety is a critical concern in dentistry. Adverse events (AEs) can harm patients, increase costs, and decrease satisfaction. Understanding AE types and frequencies is crucial for effective risk management and quality improvement. This study analyzes incident reports to identify preliminary incident patterns as a starting point for developing risk management strategies. However, under-reporting limits the ability to identify true incident patterns, highlighting the need for improved reporting systems and encouragement of incident reporting. Further research is underway to develop such a system and promote reporting to ensure sufficient data quality for effective risk management. Methods A retrospective analysis of 1,618 incident reports from December 2018 to August 2023 was conducted. A validated classification system, developed from a 5-year retrospective analysis and approved by 14 experts, categorized patient safety incidents, aligning with Thailand's Hospital Accreditation standards. Descriptive statistics summarized AE frequency and distribution. Results Of the reports, 752 were patient safety, 503 personnel safety, and 363 organizational safety incidents. Top patient safety incidents included medical record errors (176), accidental damage (66), post-operative complications (65), medical emergencies (64), and communication errors (53). Personnel safety incidents involved inappropriate working conditions (135) and work-related injuries with contact transmission risk (117). Organizational safety incidents mainly concerned policy and operational processes (131). Conclusions This study reveals the preliminary patterns of adverse events (AEs) in dental settings and underscores the limitations due to under-reporting, which affect the ability to fully understand true incident patterns. To effectively manage risks, there is a critical need for improving the existing incident reporting system and encouraging a culture of comprehensive reporting among dental professionals. Future efforts should focus on enhancing reporting systems to ensure high-quality data, enabling better identification of incident trends and supporting targeted risk management strategies to improve patient safety in dentistry.